Social Media: A Phenomenon to be Analyzed. (29th April 2015) - boyd, danah
The phenomenon of "social media" has more to do with its cultural positioning than its technological affordances. Rooted in the broader "Web 2.0" landscape, social media helped engineers, entrepreneurs, and everyday people reimagine the role that technology could play in information dissemination, community development, and communication. While the technologies invoked by the phrase social media have a long history, what unfolded in the 2000s reconfigured socio-technical practices in significant ways. Reflecting on the brief history of social media, this essay argues for the need to better understand this phenomenon.